THE IMPORTANCE OF MODERN PEDAGOGICAL TECHNOLOGIES IN TEACHING ENGLISH - Siddikova Sogdiana Mahammat Soli kizi (TADQIQOTLAR, 2026)
Abstract: This article analyzes the role and importance of modern pedagogical technologies in the process of teaching English. In particular, the effectiveness of interactive methods, information and communication technologies, multimedia tools and innovative approaches in the quality of education and the development of students’ language skills is highlighted. During the study, it was determined that modern technologies serve to increase students’ independent thinking, communicative competence and motivation. The advantages of using digital platforms in teaching English are also shown.